MCG4308 DGD #2

Question 1
For the spring-mass system shown in the diagram use x, the displacement of the mass from the spring unstretched length, as the coordinate of choice. In the diagram, l is the unstretched length of the spring. a) Derive the equation of motion using Newton's second law b) Derive the equation of motion using conservation of energy.

solution a) Using Newton First, draw a free-body diagram and remember the definition of the coordinate:

Spring force is Fspring = Kk \$ x

Newton: F = m \$ a which becomes: .. .. Fspring CFgravity = m \$ a = m\$x 2 Kk \$ x Cm \$ g = m\$x The equation of motion is .. m\$x Ck \$ x = m \$ g a) Using Conservation of energy . 1 Kinetic Energy is given by T := \$m\$ x 2 : 2 Potential Energy is given by sum of elastic and gravitational potential energies V = Vspring CVgravity

1) Divide through by x t and bring constant term to the right hand side: (1.2) Question 2 For the spring-mass system shown in the diagram.1) simplify . b) Derive the equation of motion using the conservation of energy.as it should be. Which is simpler? Why is gravity not present with this choice of coordinate? solution a) Using Newton Draw a free-body diagram and remind yourself of the definition of the coordinate: . a) Derive the equation of motion using Newton's second law.V := 1 \$k\$x t 2 Km\$g\$x t : 2 (Why Kmgx instead of Cmgx ? For positive x (downwards). (1. m d x t dt2 2 Ck x t Km g = 0 (1. c) Compare the equations you got to the answer you got in Question 1. Note that xd t is the displacement from equilibrium. use xd as the coordinate of choice. Cm \$ g x d2 m x t Ck x t = m g dt2 This is the same equation of motion we got with Newton -. the system loses gravitational potential energy) d dt T CV = 0 so: Conservation of energy implies simplify d dt T CV = 0 d x t dt .

(2.2). the right hand side becomes 0 and the equation simplifies to . m\$xd Ck \$ xd = m \$ g Kk \$ xs But using the equilibrium condition of equation (2.2) (2.2) V := subs xd = xd t ...1). . Fspring CFgravity = m \$ a = m\$xd 2 Kk \$ xd Cxs Cm \$ g = m\$xd The equation of motion is .1). this value needs to be found.With this definition of coordinate the spring force is Fspring = Kk \$ xs Cxd Since the definition of coordinate depends on the static equilibrium displacement xs . xs xs = mg k (2.1) Tell maple that xd is a function of time and that xs is given by equation (2. V 1 mg k xd t C 2 k Which can be expanded and simplified as expand (2.3) . m\$xd Ck \$ xd = 0 a) Using Conservation of energy .1).3) 2 Km g xd t (2.. This is found from writing the static equilibrium force-balance equation: m \$ g = k \$ xs m g = k xs Newton: F = m \$ a becomes: . 1 Kinetic Energy is given by T := \$m\$ xd 2 : 2 Potential Energy is given by sum of elastic and gravitational potential energies V = Vspring CVgravity 1 \$ k \$ xd Cxs 2 Km \$ g \$ xd : V := 2 From equation (2. we can solve for the value of xs as xs = solve (2..

d) What is the natural frequency of vibration? what role does gravity play in the vibrations? . x d . gravity appears in equation of motion. Find the equivalent mass of the system. Here. by choosing the coordinate as a displacement from equilibrium.5) simplify . In other words.4) is of the form (2. that is driving the motion. m d2 xd t dt2 Cxd t k = 0 (2. It is called a simple pendulum because all the mass is concentrated at the end of the string. For this system: a) Derive the equation of motion using Newton's method b) Derive the equation of motion using conservation of energy. If gravity drives the motion (like in a pendulum). then gravity will always appear in the equation of motion. not gravity.4) 1 \$ k \$ x2 CConstant and this constant will get differentiated out when writing d 2 conservation of energy in time. for this problem: gravity 2sets location of equilibrium 2 choose coordinate as displacement from equilibrium 2no gravity in equation of motion. If coordinate is not chosen as displacement from equilibrium (question 1). Question 3 Consider the simple pendulum shown in the figure. c) Use the small angle approximation to linearize the equation of motion and to find the equivalent stiffness. c) The equations in this question are the same as those in question 1 with the exception of the mg constant term on the right hand side of the equations in Q1.6) This is the same equation of motion we got with Newton.1 1 m2 g2 k xd t 2 C 2 2 k Equation (2. Conservation of energy implies d simplify T CV = 0 dt d x t dt d Divide through by xd t to clean up: (2. the presence of gravity disappears from equation of motion. it's the spring. This is due to the slightly different choice of coordinate as being a displacement from equilibrium.5) m d2 xd t dt2 Cxd t k = 0 (2. In this problem. because gravity only affects the position of the static equilibrium.

2 The kinematic constraint is that the length of the string stays constant to that r = r = 0. aθ = r\$ θ C2\$r\$θ . . . This shows how gravity can be broken down into r and θ directions. Then Newton's second law can be written in terms of polar coordinates so now the forces acting on the point mass as well as the accelerations in polar coordinates are required in the r and θ direction.a) Newton's Method Given the kinematic constraints of the system (the string doesn't change length) the best choice of coordinate to describe the state of the system is the angle θ that the string makes with the vertical.. So Newton's second law in the r direction gives: Fr = m \$ ar which becomes m \$ g \$ cos θ K T =K m\$L\$θ .2) .. the expressions for accelerations in the r and θ directions have special forms: . Remember that in polar coordinates. 2 .1) m g cos θ KT = K L m Newton's second law in the θ direction gives d θ t dt (3. r = L.. ar = r K r\$θ . Fr = m ar 2 (3. .

4) and then use that in equation (3.5) dt b) Energy Method .2) does not help us solve for θ t as the tension in the string is not known. So the kinetic energy is . first write the kinetic .equation of motion and equivalent mass To use conservation of energy to write the equation of motion.7) 2 dt 2 dt meq = solve (3. Notice that the only velocity the mass has is in the θ direction and is given by v = L\$θ.3) is the equation of motion that we want (it tells us how θ changes in time) and can be rearranged and cleaned up: .2).2) to find the tension in the string as a function of time.K m \$ g \$ sin θ = m\$L \$ θ K g sin θ = m L m d2 θ t dt2 (3.equate T to the standard form for kinetic energy: . g θC \$ sin θ = 0 L 2 g sin θ d θ t C =0 (3. 1 2 T = \$meq\$θ 2 2 2 1 d 1 d m L2 θ t = meq θ t (3.6) 2 dt From this expression it is easy to find the equivalent mass of this system -. the proper procedure is to solve for θ t from equation (3. T 2 d T = m g cos θ Cm L θ t (3. Rather.8) Taking datum from the bottom in the "swing" path of the mass: V := m\$g\$L\$ 1Kcos θ t . T = solve (3. (3. meq meq = m L2 Potential energy is due to gravitational potential energy.and potential energies.7). Equation (3. 1 T := \$m\$ L\$θ 2 2 2 1 d m L2 θ t (3..3) .4) 2 L dt Equation (3..

the smaller the number: 0.25 0.54 = 0.14). we can find the equivalent stiffness of the system as keq = m\$g\$L.V 2 2 1 mgLθ 2 2 θ 2 2 (3.11) Which is the same equation we got with Newton. The equation of motion is found from conservation of energy m L2 simplify (3. if we take cos θ z 1.13) For small values of θ. However. higher powers of θ becomes smaller and smaller numbers -. θ = 0. The higher the power. we can still find the (nonlinear) equation of motion using conservation of energy. So what we need to do is to take the first two terms of the taylor series for cos θ : cos θ z 1 K Using this. then this gives us V = 0.10) θ\$ m\$ L .12) (3. with this form of potential energy. θ = 0. the usual small angle approximation is to take only the the first terms in the taylor series so that for small θ sin θ z θ cos θ z 1 For our expression for the potential energy though. the kinematics assumption made that L stays constant doesn't work anymore. 9 cos θ = 1 K 6 8 9 1 2 1 4 1 1 θ C θ K θ C θ CO θ 2 24 720 40320 (3. then the potential energy expression becomes V := subs cos θ t θ = 1K .to see this try taking higher and higher powers of small numbers.125 0.equation of motion and equivalent stiffness The sine and cosine functions have their own Taylor/Maclaurin series about the origin: sin θ = taylor sin θ . if you don't have it.) c) Linearize with the small angle approximation . Note that the energy method does not give you any information about the tension (which is a constraint force -.9) This form of potential energy is not in the right form to find the equivalent stiffness of the system -. 9 5 7 9 1 3 1 1 sin θ = θ K θ C θ K θ CO θ 6 120 5040 cos θ = taylor cos θ .e.52 = 0.0625 Because of this.14) Clearly from equation (3.i.10) d θ t dt d2 dt2 θ t Cm g L sin θ t L d2 θ t dt2 Cg sin θ t =0 (3.we need to linearize to get rid of the cos θ term to do that (see next part). d dt T CV = 0 d θ t dt =0 (3. which is clearly nonsense.53 = 0. Using the small angle approximation sin θ z θ in the equation of motion also gives us a linear equation of motion as .m g L 1 Kcos θ t (3.

16) (3. from which we can deduce the natural frequency of the pendulum as keq ωn = meq ωn = ωn = subs meq = m\$L2. keq meq ωn = g L (3.15) Alternatively. mass M and moment of inertia IC about its mass centre.15).subs sin θ = θ t . gravity is the restoring force and kind of acts like a linear spring to restore the mass back to its equilibrium position at the bottom of the swing. (b) What is the equivalent mass of this system? . So. keq = m\$ g\$ L. keq = m\$ g\$ L.17) keq meq (3. In this problem. The link has mass m and inertia IL about its mass centre. Question 4 Consider the cylinder in the figure with radius R. Interestingly.17) and helps determine the natural frequency of the oscillations. (a) Derive the equation of motion of the cylinder. (3. gravity appears directly in the calculation of natural frequency as seen in (3. It rolls on a semicircular track of radius r without slipping. the natural frequency of vibration can be seen from the linearized equation of motion given in (3. Its axle moves in a frictionless slot in a link.4) gθ t d2 θ t C =0 2 L dt d) Natural Frequency of vibration So we have shown that meq = m\$L2. the mass does not contribute at all to the frequency of oscillation.

1) . 2 \$ 2 θ meq = IC L2 R 2 CM L2 CIL C 1 m L2 4 (4. The easiest approach to deriving the equation of motion is to use the fact that the system is conservative. So: KE := .2) meq = . 1 1 1 L . . So the no-slip kinematic relationship we want is L\$θ = R\$φ . vedge =.3) can be used to write a short-hand. The kinetic energy is the sum of the translational KE of the centres of mass of the cylinder and link and then the sum of their rotational KEs about the centre of mass. This gets us out of having to find the reactions forces between the link and the cylinder if we were to use Newton's method.6) The equation of motion can then be found from the conservation of total mechanical energy. The tangential velocity of a point on the edge of the cylinder is then the vector sum of the velocity of the centre + the relative velocity of the edge to the centre. 1 \$ IC \$ φ 2 2 C . thus must be zero.4) (4. diff R 2 2 1 IC L 1 1 1 d C M L2 C IL C m L2 θ t (4. KE . So we need to find the kinetic and potential energy of the system.2) 2 R2 2 2 8 dt So from this we can actually find the equivalent mass of the system as (4. . Because of the no-slip condition.5) (4. \$M\$ L\$θ 2 C \$IL\$ θ 2 C \$m\$ \$θ 2 2 2 2 2 2 1 I 2 C d φ t dt C 1 M L2 2 d θ t dt 2 C 1 I 2 L d θ t dt 2 C 1 m L2 8 d θ t dt 2 (4.No-slip kinematics . which means from . compact version of the kinetic energy as .3) So that equation (4. The translational velocity of the centre of the cylinder is L\$θ. 1 KE := \$meq\$ θ 2 2 2 1 d meq θ t 2 dt The potential energy is all gravitational potential energy: m\$ g\$ L PE := M\$ g\$ L\$ 1 Kcos θ C \$ 1 Kcos θ 2 1 M g L 1 Kcos θ C m g L 1 Kcos θ 2 This can also be collected and cleaned up 1 PE := MC \$ m \$ g\$ L\$ 1 Kcos θ t 2 MC 1 m g L 1 Kcos θ t 2 (4. In other words vedge = vG Cvedge \G . L . L\$θKR\$φ = 0 . Substitute the no-slip kinematic condition into the expression for kinetic energy and collect in terms of θ : . collect subs φ = \$θ.

10).3). sin.7) Dividing through by θ and collecting gives 2 \$ (4.8) 2 MCm g L θ t C2 meq The natural frequency of the linearized system is given as keq ωn = meq ωn = subs (4. KE CPE = 0 d2 θ t dt2 C2 g L sin θ t MCg L sin θ t m =0 (4.d dt which becomes simplify diff KE CPE.12) (4. use 2 θ cos θ z 1 K in the potential energy and sin θ z θ to linearize the equation of motion. PE 2 2 1 1 V= MC m gLθ (4. collect . The same linearization trick used in the previous question can also be used here. So the potential 2 energy becomes 2 θ V = subs cos θ t = 1K .7) .13) CM L2 CIL C .11) keq meq 1 m gL 2 1 m L2 4 (4.9) 2 2 From which we can clearly see by comparing to the standard form for elastic potential energy that m keq = MC \$g\$L 2 1 keq = MC m g L 2 The equation of motion is also linearized as subs sin θ t = θ t .8) Note that because of the sine term that this is a nonlinear equation.10) d2 θ t dt2 =0 (4. (4. L. (4. Namely. t = 0 1 d θ t 2 meq 2 dt .12) MC ωn = IC L R 2 2 (4. (4. g θ 2 MCm g L sin θ t C2 meq d2 θ t dt2 =0 (4.